The Assessment of Knowledge, Attitudes, and Practices of University’s Students Towards Covid 19 - Emiljano Pjetri; Edona Haxhija; Arketa Pllumi Guli; Zamira Shabani; Nertila Podgorica (Albanian Journal of Trauma and Emergency Surgery, 2024)
Introduction: The COVID - 19 has been a global public health concern from day one till now.